Entrepreneurship Education and Entrepreneurial Intention: Investigating the Moderating Role of Psychological Capital in a Tunisian Case Study - Hana, Abidi (Journal of Cultural Analysis and Social Change, 2025)
Entrepreneurship education is widely recognized as a key driver of entrepreneurial intention, yet the psychological mechanisms that shape this relationship remain insufficiently explored, particularly in emerging economies. This study investigates the effect of entrepreneurship education on entrepreneurial intention, with a specific focus on the moderating role of psychological capital within the Tunisian context. Using a quantitative approach, data were collected from university students enrolled in entrepreneurship-related programs across several Tunisian institutions. Structural equation modeling (SEM) was applied to examine the direct and conditional effects. The findings reveal that entrepreneurship education significantly enhances students’ entrepreneurial intention. Moreover, psychological capital—comprising hope, resilience, optimism, and self-efficacy—strengthens this relationship, indicating that students with higher psychological capital derive greater benefits from entrepreneurial learning experiences. These results highlight the importance of integrating psychological-capital–building components into entrepreneurship curricula to foster more robust entrepreneurial mindsets. The study contributes to the literature by providing empirical evidence from Tunisia and offers practical implications for educators, policymakers, and entrepreneurship program designers aiming to cultivate future entrepreneurs.